Using Heuristic Rules from Sentence Decomposition of Experts' Summaries to Detect Students' Summarizing Strategies - Idris, N.; Baba, S.; Abdullah, R. (2008)
Summarizing skills have been introduced to English syllabus in secondary school in Malaysia to evaluate student's comprehension for a given text where it requires students to employ several strategies to produce the summary. This paper reports on our effort to develop a computer-based summarization assessment system that detects the strategies used by the students in producing their summaries. Sentence decomposition of expert-written summaries is used to analyze how experts produce their summary sentences. From the analysis, we identified seven summarizing strategies and their rules which are then transformed into a set of heuristic rules on how to determine the summarizing strategies. We developed an algorithm based on the heuristic rules and performed some experiments to evaluate and support the technique proposed.